An Information Systems Model of the Determinants of Electronic Health Record Use - Messeri, P.; Khan, S.; Millery, M.; Campbell, A.; Merrill, J.; Shih, S.; Kukafka, R. (Applied Clinical Informatics, 2013)
Objectives: The prominence given to universal implementation of electronic health record (EHR) systems in U.S. health care reform, underscores the importance of devising reliable measures of factors that predict medical care providers’ use of EHRs. This paper presents an easily administered provider survey instrument that includes measures corresponding to core dimensions of DeLone and McClean’s (D & M) model of information system success.Methods: Study data came from self-administered surveys completed by 460 primary care providers, who had recently begun using an EHR.Results: Based upon assessment of psychometric properties of survey items, a revised D&M causal model was formulated that included four measures of the determinants of EHR use (system quality, IT support, ease of use, user satisfaction) and five indicators of provider beliefs about the impact on an individual’s clinical practice. A structural equation model was estimated that demonstrated a high level of inter-correlation between the four scales measuring determinants of EHR use. All four variables had positive association with each of the five individual impact measures. Consistent with our revised D&M model, the association of system quality and IT support with the individual impact measures was entirely mediated by ease of use and user satisfaction.Conclusions: Survey research provides important insights into provider experiences with EHR. Additional studies are in progress to investigate how the variables constructed for this study are related to direct measures of EHR use.Citation: Messeri P, Khan S, Millery M, Campbell A, Merrill J, Shih S, Kukafka R. An information systems model of the determinants of electronic health record use. Appl Clin Inf 2013; 4: 185–200http://dx.doi.org/10.4338/ACI-2013-01-RA-0005
Keywords: Electronic health records; health information technology; EHR evaluation; provider assessment of EHR quality